Quantifying the structure and dynamics of fish shoals under predation threat in three dimensions. (18th November 2019) - Romenskyy, Maksym; Herbert-Read, James E; Ioannou, Christos C; Szorkovszky, Alex; Ward, Ashley J W; Sumpter, David J T
Abstract: Detailed quantifications of how predators and their grouping prey interact in three dimensions (3D) remain rare. Here we record the structure and dynamics of fish shoals ( Pseudomugil signifer ) in 3D both with and without live predators ( Philypnodon grandiceps ) under controlled laboratory conditions. Shoals adopted two distinct types of shoal structure: "sphere-like" geometries at depth and flat "carpet-like" structures at the water's surface, with shoals becoming more compact in both horizontal and vertical planes in the presence of a predator. The predators actively stalked and attacked the prey, with attacks being initiated when the shoals were not in their usual configurations. These attacks caused the shoals to break apart, but shoal reformation was rapid and involved individuals adjusting their positions in both horizontal and vertical dimensions. Our analyses revealed that targeted prey were more isolated from other conspecifics, and were closer in terms of distance and direction to the predator compared to non-targeted prey. Moreover, which prey were targeted could largely be identified based on individuals' positions from a single plane. This highlights that previously proposed 2D theoretical models and their assumptions appear valid when considering how predators target groups in 3D. Our work provides experimental, and not just anecdotal, support for classic theoretical predictions and also lends new insights into predatory–prey interactions in three-dimensional environments. Abstract : This research investigates how predatory fish attack fish shoals in three dimensions. It finds that some of the previously criticized assumptions of theoretical models remain valid when considering how predators attack prey in 3D. The work offers new insights into how predators and prey interact in three dimensions.